THE USE OF MEMRISE APPLICATION ON STUDENTS’ MOTIVATION IN LEARNING ENGLISH VOCABULARY - Deputri, Anisa Bela; Hamidiyah, Aisyah; Baihaqi, Akhmad (GENTA BAHTERA: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2023)
This study aimed to determine the influence of the Memrise application on students’ motivation to learn English vocabulary among 8th-grade students at SMPN 24 Kota Serang, Banten Province. This research used quantitative research with a quasi-experimental design. This study involved experimental and control classes that were selected by purposive sampling technique. The instruments in this study were a questionnaire and observation. The results showed the significance value of the post-test from the questionnaire and behavioral observation for the experimental and control classes with a sig (2-tailed) was 0.000, which means <0.05. The effect value of the questionnaire and behavioral observation results was 4.42, and it was included in high effect criteria. It shows that the alternative hypothesis was accepted, which concludes that the Memrise application has an influence on students’ motivation to learn English vocabulary in the 8th grade at SMPN 24 Kota Serang.